Developments in Dye-Sensitized Solar Cells - An Overview - Pugazhenthiran N.; Kandasamy M.; Sathishkumar P.; Suresh S.; Karthick Kumar S.; Murugesan S. (Elsevier, 2025)
Development of dye-sensitized solar cells (DSSCs) has been marked by significant advancements in recent years and driven by innovative approaches in several key areas. Photoanode modification plays a pivotal role in improving the efficiency of DSSCs. Researchers have explored various strategies, including the use of novel materials, optimized sensitizers, and advanced nanostructures. These modifications have led to enhanced light absorption, charge separation, and electron transport within the DSSCs. Recent breakthroughs in materials engineering and encapsulation techniques have significantly extended the operational lifetimes of DSSCs and brought them closer to practical applications. Furthermore, transferring DSSC technology from laboratory to industrial-scale production has been a focus of research and development. Scalability, cost-effectiveness, and process optimization have been addressed, enabling the transition from lab-scale prototypes to mass production. Prototype DSSC devices have evolved to meet the demands of real-time applications. These include transparent and flexible DSSC modules that can be integrated into architectural designs, portable electronics, and IoT devices. Moreover, commercialization efforts have gained momentum, with several companies exploring the integration of DSSCs into building materials, consumer electronics, and other real-world applications. In this context, this chapter provides an overview of the developments of DSSCs, focusing on photoanode modification, stability enhancement, commercialization efforts, scaling from laboratory to industry, prototype device design, and real-time applications that have made significant strides in recent years. These advancements positioned DSSCs as a promising and sustainable solar technology with the potential to address various energy demands in the future. ? 2024 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.